Codex 2400 and Its Miniatures - Willoughby, Harold R. (Analecta Gorgiana, 2013)
This work contains illustrations of the thirteenth century Byzantine New Testament at the Rockefeller-McCormack collection in Chicago with a full description of its text, provenance, and the artistic and theological significance of the miniatures.